Analisis Dampak Ekonomi Terhadap Kesejahteraan Masyarakat di Kawasan Pesisir Wisata Hiu Paus Desa Labuhan Jambu Kabupaten Sumbawa: Dampak Ekonomi, Kesejahteraan Masyarakat - Sri Rahayu; Sri Nurhidayati; Nila Wijayanti; Ieke Wulan Ayu; Edrial (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to analyze the economic impact on the welfare of the community around the Whale Shark area in the village of Labuhan Jambu. The current condition of the movement of the tourism industry in Labuhan Jambu Village is still not optimal. In addition to weak promotion, there are limited tourism support facilities and limited quality of human resources in managing tourism. The research method uses a quantitative descriptive approach. Source of data consists of secondary data and primary data. Data collection techniques are questionnaires, observation and documentation. The data analysis technique in this study uses structural equation modeling analysis. The results of the study indicate that there is no direct influence felt by the community as a whole from the existence of Whale Shark ecotourism on the community's economy and the welfare of the surrounding community. The direct influence is only felt by chart owners and operators of Whale Shark ecotourism, that chart owners and operators who deal directly with tourists who visit Whale Shark tours in the village of Labuhan Jambu. For tourists who rarely go ashore, the route used is the sea route. The tourists only stop for 1 to 2 hours to see the Whale Shark ecotourism, after which the tourists go straight to the next tourist spot, namely Komodo Island. This makes the community, especially business actors, not get a significant impact from Whale Shark ecotourism.